Factors Affecting The Building Of The Accounting Information Systematsmall And Medium Enterprises (Smes) In Dong Nai Province - THU HIEN, LY THI (Social Science Learning Education Journal, 2017)
Small & Medium Enterprises (SMEs) play an important role in the economic development of a country. Their role in terms of production, employment generation, contribution to exports & facilitating equitable distribution of income is very critical.Besides, the Accounting Information System (AIS) form is an integral part of modern organizations since they support managers to plan and control business operations, improve decision-making in organizations, and support financial accounting and reporting. The studyresults showed that there were 300 accounting managers of SMEs in Dong Nai province whointerviewed and answered about 11 questions. Data collected from July 2016 to March 2017forSmall & Medium Enterprises in Dong Nai province. The study had been analyzed Cronbachs Alpha,KMO test, and the result of KMO analysis used for multiple regression analysis. Accounting managersâ responses measured through an adapted questionnaire on a 5-point Likert scale (Conventions: 1: Completely disagree, 2: Disagree, 3: Normal; 4: Agree; 5: completely agree). Hard copy and online questionnaire distributed among 2.000 accounting managers of Small & Medium Enterprises (SMEs) in Dong Nai province. In addition,the exploratory factor analysis (EFA) results showed that there were two environments, which included of environment following internal environment (X1) andexternal environment(X2) with significance level 5 percent. In addition, all of two components affecting the building of the accounting information system at Small & Medium Enterprises (SMEs) in Dong Nai province with significance level 5 percent. The research results processed from SPSS 20.0 software.